Microstructure-dependent ferroelectric properties of SrBi2Ta2O9 thin films fabricated by radio frequency magnetron sputtering - Cho, KJ; Lee, JK; Jung, HJ; Park, JW (A V S AMER INST PHYSICS, 1998)
Microstructure dependencies on the ferroelectric properties of SrBi2Ta2O9 (SBT) thin films were observed by changing the sputtering pressure in the rf magnetron sputtering technique. The microstructure and the crystal orientations were determined by the compositional change of the films, which was controlled by the scattering behaviors during sputter depositions. The good ferroelectric hysteresis loop behavior was due to the stoichiometric composition and the layered perovskite structure of the SET thin films. On the other hand, nonstoichiometric SET films had small grains of pyrochlore structure and linear dielectric behavior. (C) 1998 American Vacuum Society.
Keywords: FATIGUE